Treatment of Binge Eating Disorder - Crow, Scott (Curr Treat Options Psychiatry, 2014)
Binge eating disorder is a common eating disorder that recently has received increasing attention. Goals in treating binge eating disorder typically include controlling binge eating and diminishing excess body weight. A variety of treatment approaches have been used, including diet/lifestyle modification, psychotherapy, and pharmacologic treatment. Diet and lifestyle interventions are somewhat effective in diminishing the binge eating behavior and lead to modest weight loss, but the weight effects are limited and not typically lasting. A number of psychotherapies have been shown to be beneficial, mostly for stopping binge eating, and tend to show little impact on weight loss. Numerous pharmacologic interventions have been developed, with the focus on antidepressants (used for their anti-binge eating effects) and weight loss drugs. Both have been shown to be helpful but again, for antidepressants, bringing about lasting weight loss appears to be difficult. The most effective approach to treating binge eating disorder (if available) is likely psychotherapy combined with medication management as indicated.